DEVELOPMENT OF SPECIAL ENDURANCE IN AMATEUR JUDO PLAYERS USING MOVEMENT GAMES AT THE INITIAL TRAINING STAGE. (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Theoretical and practical substantiation of the effectiveness of the methodology for developing special endurance through the use of mobile games in the training process of young judokas at the initial stage of training.